Modelling as a fundament for creativity - Frisch, Nina Scott (FormAkademisk, 2018)
The overall setting around this investigation is the writing of a PhD thesis ‘To see the visually controlled’ (Frisch, 2010), where my aim was to document, describe, analyse, compare and theorise formal (teacher-initiated) and informal (children-initiated) visually controlled drawings, also called modelling drawing processes, among 9–12-year-olds. The modernist narrative in art education presented by Wilson (2004) claims that modelling in drawing among children is uncreative. My investigation shows how creative processes can be detected by using Vygotsky’s creativity theory and Kaufmann and Beghetto’s (2009) 4c creativity model within a sociocultural theoretical tradition. The acts of creative processes done by moving modelled elements in a drawing around has not been thoroughly seen as a central strategy in children´s drawing processes. This article is an attempt to shed light on these processes often found when looking at children’s informal drawing processes. The importance of these ‘shifting-around’ processes are not always regarded as valuable and related to both modelling and creativity. The relation between modelling in drawing and creativity as part of children´s drawing learning is explored in this article.